Assessment of the behavior of Rosa rubiginosa seed waste during slow pyrolysis process towards complete recovery: Kinetic modeling and product analysis. (15th November 2022) - Torres-Sciancalepore, Rodrigo; Asensio, Daniela; Nassini, Daniela; Fernandez, Anabel; Rodriguez, Rosa; Fouga, Gastón; Mazza, Germán
Graphical abstract: Highlights: Rosehip seed waste thermal decomposition was described in three parallel reactions. Activation energies were between 167.96 kJ/mol and 210.16 kJ/mol for all reactions. Gaseous pyrolysis products included CO, CO2, CH3 OH, CH4 and H2 . Phenolic compounds such as eugenol, guaiacol and cresols were found in tar product. Abstract: The aim of this work was to analyze the exhausted waste of sweet briar rosehip seeds (RSW) from an oil production industry in order to study its pyrolysis kinetics and the products obtained, for evaluation of its potential for thermochemical processes with the aim of achieving total recovery. Pyrolysis modeling by deconvolution showed the existence of four processes: one related to the loss of remaining moisture, and three pyrolysis reactions linked to the decomposition of hemicelluloses, cellulose and lignin. Activation energy was 62.08 kJ/mol for physical evaporation, and 167.96 kJ/mol, 266.28 kJ/mol and 210.16 kJ/mol for the pyrolysis of hemicelluloses, cellulose, and lignin, respectively. The kinetic model that best fit the experimental data was the reaction order with n between 3 and 4.8 for the pyrolysis reactions and n = 2.8 for moisture evaporation. Gases released were CO2, CO, CH4, H2, CH3 OH, and water vapor. The highest production of CO2 and CO occurred at 300–350 °C, mainly due to the decomposition of hemicelluloses and cellulose, while the highest production of H2 and CH4 occurred from 350 to 400 °C onwards, mainly as a consequence of lignin decomposition. A total 59 compounds were identified in tar products by GC–MS, most of them phenolic by lignin rupture. SEM analysis of the biochar showed an increase in pore size and interstices on the surface with temperature. The SEM-EDS and XRD analysis of ashes showed high Ca content (53.02 %), with Ca being present in compounds such as hydroxyapatite, portlandite, magnesian calcite and KCaPO4 . The study demonstrated the potential of RSW for recovery through thermochemical methods, also revealing the decomposition kinetics in an inert atmosphere, which need to be known for designing pyrolysis, gasification or combustion power plants.